Transgenerational transmission of small‐for‐gestational age. (3rd May 2019) - Sepúlveda‐Martínez, Á.; Rodríguez‐López, M.; Paz Y Miño, F.; Casu, G.; Crovetto, F.; Gratacós, E.; Crispi, F.
ABSTRACT: Objective: To evaluate the transgenerational transmission of small‐for‐gestational age (SGA). Methods: This was a cohort study of a random sample of 2043 offspring delivered between 1975 and 1993 at Hospital Sant Joan de Déu in Barcelona. Exclusion criteria were multiple pregnancy, aneuploidy or genetic syndrome, major birth defects, severe mental disease and macrosomia. Eligible individuals were contacted and those with at least one offspring were included in the study. Participants were classified according to the presence of SGA (defined as birth weight < 10 th percentile) at birth. Multiple regression analysis was used to determine the presence of SGA or placenta‐mediated disease (defined as the presence of SGA, pre‐eclampsia, gestational hypertension and/or placental abruption) in the following generation. Results: Of 623 individuals who agreed to participate, 152 (72 born SGA and 80 born appropriate‐for‐gestational age (AGA)) were reported to have at least one child. Descendants of SGA individuals presented with a lower birth‐weight percentile (median, 26 (interquartile range (IQR), 7–52) vs 43 (IQR, 19–75); P < 0.001) and a higher prevalence of SGA (40.3% vs 16.3%; P = 0.001) and placenta‐mediated disease (43.1% vs 17.5%; P = 0.001) than did the offspring of AGA individuals. After adjustment for confounding variables, parental SGA background was associated with an almost three‐fold increased risk of subsequent SGA or any placenta‐mediated disease in the following generation. This association was stronger in SGA mothers than in SGA fathers. Conclusions: Our data provide evidence suggesting a transgenerational transmission of SGA, highlighting the importance of public health strategies for preventing intrauterine growth impairment. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.